Sparsity-based AOA Estimation for Emitter Localization - Lingwen Zhang (Institute of Advanced Engineering and Science, 2012)
Angle of arrival (AOA) is able to achieve high accuracy when the antenna arrays are deployed much closer to the emitter. However, spatial resolution problem still exists. This paper presents a novel AOA estimation method called sparsity angle sensing (SAS) to improve the resolution. It integrates compressive sensing theorem into the parameter estimation formula. Traditional approaches for AOA estimation such as beamforming (BF), minimum variance distortionless response (MVDR), multiple signal classification (MUSIC) are compared with SAS, and simulation results are discussed. It is shown that SAS method outperforms the other three methods in spatial resolution and robustness. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.867